The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1094/cchem-08-11-0103
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of β‐Glucan from Oats for Soluble Dietary Fiber Quality Analysis

Abstract: Extraction protocols for β‐glucan from oat flour were tested to determine optimal conditions for β‐glucan quality testing, which included extractability and molecular weight. We found mass yields of β‐glucan were constant at all temperatures, pH values, and flour‐to‐water ratios, as long as sufficient time and enough repeat extractions were performed and no hydrolytic enzymes were present. Extracts contained about 30–60% β‐glucan, with lower proportions associated with higher extraction temperatures in which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition to peaks eluting in the order T > TA > TAF due to decreasing M w , the polydispersity index (M w /M n ) increased in the order T < TA < TAF, indicating a broadening of the molecular mass distribution in the samples as a result of intensified enzymatic treatment. In a similar study Doehlert et al (2012) found starch hydrolytic enzymes to have a large effect on the M w and polydispersity when used for maximizing the extractability of oat BGs. Hence, efficient BG extractability and recovery must be balanced against M w loss of the extracted BG when using existing enzyme preparations.…”
Section: Molecular Mass and Viscositymentioning
confidence: 89%
See 3 more Smart Citations
“…In addition to peaks eluting in the order T > TA > TAF due to decreasing M w , the polydispersity index (M w /M n ) increased in the order T < TA < TAF, indicating a broadening of the molecular mass distribution in the samples as a result of intensified enzymatic treatment. In a similar study Doehlert et al (2012) found starch hydrolytic enzymes to have a large effect on the M w and polydispersity when used for maximizing the extractability of oat BGs. Hence, efficient BG extractability and recovery must be balanced against M w loss of the extracted BG when using existing enzyme preparations.…”
Section: Molecular Mass and Viscositymentioning
confidence: 89%
“…However, introducing more enzymes to a process increases the risk of hydrolytic side-, or contaminating activities on BGs. Few studies using enzymes as part of their BG isolation have investigated, if the amylolytic enzymes had any effect on the BG itself (Benito-Roman et al, 2014;Doehlert et al, 2012). In the present study we screen widely different barley genotypes for BG extraction yields.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations